Postawy młodzieży względem zaangażowania szkolnego rodziców: kontekst stosunków między rodzicami a nauczycielami - Biber, Zohar (Studia Edukacyjne, 2020)
Since the concept of the ‘school’ has existed, the triangle of parents, teachers, and students, in all that relates to the parental involvement in the school, has constituted a significant factor that saw ‘ups and downs’ over the years. Some supported the separation between the student’s home and the school, while others saw the connection and cooperation between them to be essential. This article examines students’ attitudes towards their parents’ involvement in school. This article will present the difficulties adolescents have with their parents’ authority and treatments for the era in which we live. Some research studies have found a correlation between parental involvement and its impact on children. The research study diagnoses the students’ positions according to quantitative questionnaires that were built and used. After analyzing quantitative questionnaires, the research attempted to draw conclusions about the tension that exists between the theories and studies showing the benefits of parental involvement regarding the results of the quantitative questionnaires.